Mengembangkan dan Menyebarkan Gagasan Perdamaian - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
This articles described various definitions of peace and peace science, and put special emphasis on operational ones which are relevant for our survival. Our main and immediate concern is the threat of a nuclear war which endangers the global ecosystem. Several reasons are brought forth why this problem has not been widely discussed in the Third World. Furthermore, the articles pointed out that old ideas on the biological necessity and unavoidability of war are obsolete and incorrect, and the assumption that nuclear arms race is just a political game to preserve peace is no longer valid. Also, the possibility of human survival after a nucleanholocallst is categorically rejected. Finally, the responsibility of the university in the preservation of peace is proposed. Key Words: peace studies - structural violence - nuclear warfare - human survival - peace-oriented education